2001
DOI: 10.1215/s1522851700000338
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between ventricular and lumbar cerebrospinal fluid cytology in adult patients with leptomeningeal metastases

Abstract: Leptomeningeal metastases (LMs) are common metastatic complications, occurring in at least 5% of patients with disseminated cancer. Cerebrospinal uid (CSF) cytology remains the standard for diagnosis and assessment of treatment response, but may be inadequate. Our objective was to compare ventricular and lumbar CSF cytology in patients who had cytologically proven LM and were receiving intra-CSF chemotherapy. Sixty patients with LM, positive lumbar CSF cytology documented at diagnosis, limited extent of CNS di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 7 publications
0
48
0
Order By: Relevance
“…The most important technical limitation of our study is that CSF samples were obtained at the time of surgery, and they were often from the ventricles rather than from a lumbar puncture. CSF has been shown to quickly circulate throughout the ventricles and spinal reservoirs (39,40). It is, therefore, very likely that the DNA in the spinal fluid obtained through lumbar puncture will be similar to that of the ventricles, although the fluid obtained from lumbar puncture is farther away from the site of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The most important technical limitation of our study is that CSF samples were obtained at the time of surgery, and they were often from the ventricles rather than from a lumbar puncture. CSF has been shown to quickly circulate throughout the ventricles and spinal reservoirs (39,40). It is, therefore, very likely that the DNA in the spinal fluid obtained through lumbar puncture will be similar to that of the ventricles, although the fluid obtained from lumbar puncture is farther away from the site of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 60 patients with NM, positive lumbar CSF cytology at diagnosis, and no evidence of CSF flow obstruction, ventricular and lumbar cytologies obtained simultaneously were discordant in 30% of cases [24]. The authors observed that, in the presence of spinal signs or symptoms, the lumbar CSF was more likely to be positive and, conversely, in the presence of cranial signs or symptoms, the ventricular CSF was more likely to be positive.…”
Section: Csf Examinationmentioning
confidence: 97%
“…Cytology of the CSF obtained by lumbar puncture is more likely to be positive than CSF obtained using a ventricular catheter if spinal cord-related symptoms are present and vice versa if cranial-related symptoms are present. 67 Periodic lumbar puncture is recommended in the follow-up of patients with neoplastic meningitis, even in those with ventricular catheters, because cytology results have high rates of false-negative results when using samples taken from ventricular catheters. 32,67 Essential elements of the CSF laboratory evaluation include cell count and differential, cytology, protein, and glucose concentrations ( Table 2).…”
mentioning
confidence: 99%
“…67 Periodic lumbar puncture is recommended in the follow-up of patients with neoplastic meningitis, even in those with ventricular catheters, because cytology results have high rates of false-negative results when using samples taken from ventricular catheters. 32,67 Essential elements of the CSF laboratory evaluation include cell count and differential, cytology, protein, and glucose concentrations ( Table 2). In patients who have primary solid tumors, a finding of malignant cells in the CSF is evidence of leptomeningeal metastases.…”
mentioning
confidence: 99%
See 1 more Smart Citation